Implementasi Model Pembelajaran Eksperiensial untuk Meningkatkan Hasil Belajar Kimia Peserta Didik SMK - Vidiastuti, Ririn; Hartono, Hartono; Kusmawaty, Dewi (FKIP Universitas Lampung, 2018)
Implementation of Experiential Learning Model to Increase SMK Students’ Learning Outcomes. This classroom action research aims to improve students' chemistry learning result of class XI TITL1 SMKN 4 Palembang through experiential learning model. The study was conducted in two cycles, each cycle consisting of two meetings. The data were obtained by using observation sheet and test instrument of student learning result which was done at the end of the meeting. Improvement of student learning outcomes can be seen from the average of student learning outcomes before the action done (T0) of 71,23 with mastery learning 42,86%, an increase in 1st cycle (T1) to 77,74 with mastery learning 62,86% and in the 2nd cycle (T2) increased to 84.23 with learning mastery 85.71%. Keywords: classroom action research, experiential model, student chemistry learning result. DOI: http://dx.doi.org/10.23960/jpp.v8.i2.201813